Penyuluhan Tentang Ispa (Infeksi Saluran Pernafasan Akut) Pada Ibu Dan Balita Wilayah Kerja Puskesmas Bukit Sari, Kecamatan Kabawetan Kepahiang - Ayu, Anggra; Sella, Vofi Tri; Elvanora, Sulasi Tahira; Yuniarti, Elza; Lince, Lili Sri; Tranado, Hengki; Rohani, Tuti; Azissah, Danur (Universitas Dehasen Bengkulu, 2025)
Acute Respiratory Tract Infection (ARI) is a disease of the upper and lower respiratory tract, this disease is often suffered by infants, children, the elderly and or people who have health problems (Malang Health Office, 2018). ARI occurs in the respiratory tract starting from the nose, middle ear, pharynx (throat), voice box (larynx), bronchi, bronchi and lungs. The types of upper respiratory tract infections are cough, runny nose, earache (otitis media) and strep throat (pharyngitis), while the types of diseases that include lower respiratory tract infections are bronchitis, bronchitis and pneumonia (POM, 2019). The purpose of the counseling that our group carried out was to provide education to the people of Hamlet 2 of Bukit Sari village. It is hoped that with this counseling, the number of people with ISPA in hamlet 2 of Bukit Sari village can decrease and even be resolved.